Immune-epithelial cell cross‐talk enhances antiviral responsiveness to SARS‐CoV‐2 in children - Gonçalves Magalhães, Vladimir; Lukassen, Sören; Drechsler, Maike; Loske, Jennifer; Burkart, Sandy S; Wüst, Sandra; Jacobsen, Eva‐Maria; Röhmel, Jobst; Mall, Marcus A; Debatin, Klaus‐Michael; Eils, Roland; Autenrieth, Stella; et al. (EMBO reports, 2023)
The risk of developing severe COVID‐19 rises dramatically with age. Schoolchildren are significantly less likely than older people to die from SARS‐CoV‐2 infection, but the molecular mechanisms underlying this age‐dependence are unknown. In primary infections, innate immunity is critical due to the lack of immune memory. Children, in particular, have a significantly stronger interferon response due to a primed state of their airway epithelium. In single‐cell transcriptomes of nasal turbinates, we find increased frequencies of immune cells and stronger cytokine‐mediated interactions with epithelial cells, resulting in increased epithelial expression of viral sensors (RIG‐I, MDA5) via IRF1. In vitro, adolescent peripheral blood mononuclear cells produce more cytokines, priming A549 cells for stronger interferon responses to SARS‐CoV‐2. Taken together, our findings suggest that increased numbers of immune cells in the airways of children and enhanced cytokine‐based interactions with epithelial cells tune the setpoint of the epithelial antiviral system. Our findings shed light on the molecular basis of children's remarkable resistance to COVID‐19 and may suggest a novel concept for immunoprophylactic treatments.